Influence of Respiratory Gating, Image Filtering, and Animal Positioning on High-Resolution Electrocardiography-Gated Murine Cardiac Single-Photon Emission Computed Tomography - Chao Wu; Pieter E.B. Vaissier; Brendan Vastenhouw; Johan R. de Jong; Riemer H.J.A. Slart; Freek J. Beekman (Molecular Imaging)
Cardiac parameters obtained from single-photon emission computed tomographic (SPECT) images can be affected by respiratory motion, image filtering, and animal positioning. We investigated the influence of these factors on ultra-high-resolution murine myocardial perfusion SPECT. Five mice were injected with 99m technetium ( 99m Tc)-tetrofosmin, and each was scanned in supine and prone positions in a U-SPECT-II scanner with respiratory and electrocardiographic (ECG) gating. ECG-gated SPECT images were created without applying respiratory motion correction or with two different respiratory motion correction strategies. The images were filtered with a range of three-dimensional gaussian kernels, after which end-diastolic volumes (EDVs), end-systolic volumes (ESVs), and left ventricular ejection fractions were calculated. No significant differences in the measured cardiac parameters were detected when any strategy to reduce or correct for respiratory motion was applied, whereas big differences (> 5%) in EDV and ESV were found with regard to different positioning of animals. A linear relationship ( p < .001) was found between the EDV or ESV and the kernel size of the gaussian filter. In short, respiratory gating did not significantly affect the cardiac parameters of mice obtained with ultra-high-resolution SPECT, whereas the position of the animals and the image filters should be the same in a comparative study with multiple scans to avoid systematic differences in measured cardiac parameters.